Fixed Coronary Artery Stenosis in Tunneled Coronary Artery Identified by Intravascular Ultrasound: A Case Report - Yuxiang Dai (Shanghai Institute of Cardiovascular Diseases, Zhongshan Hospital, Fudan University, Shanghai, China) (AgiAl Publishing House, 2018)
Myocardial bridging is characterized as the compression of a segment of the coronary artery during systole. Significant atherosclerosis within the bridge is almost never seen at pathologic examination because of the absence of synthetic type smooth muscle cells in the intima of the tunneled artery. To date, there have been no reports of significant atherosclerosis at the site of myocardial bridging documented by angiography or intravenous ultrasound. We report a rare case of fixed coronary artery stenosis at the site of myocardial bridging identified by intravascular ultrasound.